Dual embryonic origin and patterning of the pharyngeal skeleton in the axolotl (Ambystoma mexicanum). Issue 3 (June 2015) - Sefton, Elizabeth M.; Piekarski, Nadine; Hanken, James
SUMMARY The impressive morphological diversification of vertebrates was achieved in part by innovation and modification of the pharyngeal skeleton. Extensive fate mapping in amniote models has revealed a primarily cranial neural crest derivation of the pharyngeal skeleton. Although comparable fate maps of amphibians produced over several decades have failed to document a neural crest derivation of ventromedial elements in these vertebrates, a recent report provides evidence of a mesodermal origin of one of these elements, basibranchial 2, in the axolotl. We used a transgenic labeling protocol and grafts of labeled cells between GFP+ and white embryos to derive a fate map that describes contributions of both cranial neural crest and mesoderm to the axolotl pharyngeal skeleton, and we conducted additional experiments that probe the mechanisms that underlie mesodermal patterning. Our fate map confirms a dual embryonic origin of the pharyngeal skeleton in urodeles, including derivation of basibranchial 2 from mesoderm closely associated with the second heart field. Additionally, heterotopic transplantation experiments reveal lineage restriction of mesodermal cells that contribute to pharyngeal cartilage. The mesoderm‐derived component of the pharyngeal skeleton appears to be particularly sensitive to retinoic acid (RA): administration of exogenous RA leads to loss of the second basibranchial, but not the first. Neural crest was undoubtedly critical in the evolution of the vertebrate pharyngeal skeleton, but mesoderm may have played a central role in forming ventromedial elements, in particular. When and how many times during vertebrate phylogeny a mesodermal contribution to the pharyngeal skeleton evolved remain to be resolved.